2012
DOI: 10.1111/j.1365-313x.2012.04985.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial‐ and plant‐type phosphoenolpyruvate carboxylase isozymes from developing castor oil seeds interact in vivo and associate with the surface of mitochondria

Abstract: SUMMARYPhosphoenolpyruvate carboxylase (PEPC) from developing castor oil seeds (COS) exists as two distinct oligomeric isoforms. The typical class-1 PEPC homotetramer consists of 107-kDa plant-type PEPC (PTPC) subunits, whereas the allosterically desensitized 910-kDa class-2 PEPC hetero-octamer arises from the association of class-1 PEPC with 118-kDa bacterial-type PEPC (BTPC) subunits. The in vivo interaction and subcellular location of COS BTPC and PTPC were assessed by imaging fluorescent protein (FP)-tagge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 51 publications
(112 reference statements)
4
21
0
Order By: Relevance
“…All tissues were frozen in liquid N 2 and stored at Ϫ80°C until used. Tobacco (Nicotiana tabacum L.) Bright Yellow-2 suspensioncultured cells were maintained and prepared for biolistic bombardment as described previously (34).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All tissues were frozen in liquid N 2 and stored at Ϫ80°C until used. Tobacco (Nicotiana tabacum L.) Bright Yellow-2 suspensioncultured cells were maintained and prepared for biolistic bombardment as described previously (34).…”
Section: Methodsmentioning
confidence: 99%
“…Transient transformation of tobacco cells with RcSUS1-EYFP and mCherry-RcPPC3 (encoding cytosolic targeted plant-type phosphoenolpyruvate (PEP) carboxylase from developing COS) (34) was performed with 5 g of each plasmid DNA using a Bio-Rad Biolistic particle delivery system. Bombarded cells were incubated for 8 h to allow for gene expression and protein sorting, fixed in 4% (w/v) formaldehyde, and imaged using epifluorescence microscopy as previously described (34).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, BTPC genes encode larger 116-to 118-kD polypeptides owing to a unique intrinsically disordered region that mediates BTPC's tight interaction with coexpressed PTPC subunits. This association results in the formation of unusual Class-2 PEPC heterooctameric complexes that are largely desensitized to allosteric effectors and that dynamically associate with the surface of mitochondria in vivo (O'Leary et al, 2009(O'Leary et al, , 2011aIgawa et al, 2010;Park et al, 2012).…”
mentioning
confidence: 99%
“…Subsequent research revealed that the native BTPC exists as a p118, but that upon COS extraction it is rapidly cleaved by an endogenous thiol endopeptidase into 54-kD and 64-kD polypeptides (p54 and p64; Gennidakis et al, 2007). BTPC's proteolytic cleavage site (Lys-446/Ile-447) as well as its in vivo Ser-425 and Ser-451 phosphorylation sites all occur within an approximate 10-kD intrinsically disordered region, a distinctive feature of green algal and vascular plant BTPCs that mediates their tight interaction with coexpressed PTPC subunits to form the Class-2 PEPC heteromeric complex (O'Leary et al, 2011b;Park et al, 2012).…”
Section: Btpc's Intrinsically Disordered Region Is An Rccdpk1 Interacmentioning
confidence: 99%